Global trends and perspectives in mitophagy on neurodegenerative diseases: a scientometric analysis over 20 years - Wu, Haiyan; Zhang, Minheng; Zhang, Lei; Liu, Hongwei; Fan, Haixia (Frontiers in Medicine, 2025)
BackgroundThe investigation of mitophagy in neurodegenerative diseases has grown significantly, yet a comprehensive global insight remains limited. This study conducts a scientometric analysis to map the research landscape related to mitophagy in neurodegenerative diseases.MethodsWe conducted a bibliometric analysis of 2,566 publications (2004 to 11 June 2025) from Web of Science Core Collection and Scopus. To mitigate bias in trend analyses, incomplete 2025 data were excluded from publication growth and curve fitting but retained for other analyses. Data were analyzed via Bibliometrix R package, VOSviewer, Scimago Graphica, and CiteSpace to map mitophagy research evolution.ResultsThe field showed exponential growth with peak productivity in 2021. The United States led publication output, with institutions from the USA, UK, and China forming the core of robust international collaborations, while maintaining the highest citation impact. Influential researchers included Tavernarakis, Nektarios and Reddy, P. Hemachandra, with prominent journals such as International Journal of Molecular Sciences, Cells and Autophagy, serving as key publication venues. Cluster analysis revealed thematic structures centered on “Parkinson’s disease,” “mitochondrial dysfunction,” “oxidative stress,” and “fission/fusion mechanisms”, with additional focus on “Parkin-mediated mitophagy” and “neurodegenerative diseases.” Research evolved from foundational studies through mechanistic exploration to translational applications. Emerging trends include “post-translational modifications (PTMs),” “chaperone-mediated autophagy,” “gut microbiota,” “mitochondrial quality control,” and therapeutic investigations of compounds like “curcumin” and “melatonin.”ConclusionThis first comprehensive scientometric analysis underscores the expanding interest in mitophagy as a crucial molecular mechanism in neurodegenerative diseases. Our findings establish a framework for developing novel therapeutic interventions such as mitochondrial quality control modulators and compounds like curcumin and melatonin targeting mitophagy dysfunction in neurodegenerative disorders.